2017
DOI: 10.1002/jhbp.420
|View full text |Cite
|
Sign up to set email alerts
|

IL‐7 and procalcitonin are useful biomarkers in the comprehensive evaluation of the severity of acute cholangitis

Abstract: The combined use of IL-7 and PCT may be useful for evaluating severe acute cholangitis; these results may suggest that severe acute cholangitis is affected by immunosuppressive changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Therefore, accurate and timely identification of AC with or without sepsis is essential for the optimal management of patients, further limiting morbidity and improving the prognosis of patients. WBC, CRP, and PCT have been widely used as biomarkers in nearly all studies of infection, but these biomarkers still have false positives and negatives in the diagnosis of infection and sepsis [7]. TREM-1 is a cell surface receptor expressed on myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, accurate and timely identification of AC with or without sepsis is essential for the optimal management of patients, further limiting morbidity and improving the prognosis of patients. WBC, CRP, and PCT have been widely used as biomarkers in nearly all studies of infection, but these biomarkers still have false positives and negatives in the diagnosis of infection and sepsis [7]. TREM-1 is a cell surface receptor expressed on myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…When AC with sepsis appears, unless appropriate biliary drainage and antibiotics are rapidly given, the systemic condition will suddenly deteriorate, which often results in mortality [4]. The 30-day mortality rate of patients with sepsis caused by AC has been reported to be ∼10% [6,7]. In the Tokyo Guidelines, the selection of an empiric antimicrobial agent is dependent on severity of cholangitis [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with high pre-biliary drainage serum creatinine is also associated with higher mortality[ 46 ]. A recent study also suggested that serum IL-7 level of less than 6.0 and serum procalcitonin level of more than 0.5 was associated with higher mortality[ 47 ].…”
Section: Prognosismentioning
confidence: 99%
“…For example, significantly elevated serum levels of cytokines were observed in bovine with clinical and subclinical mastitis (including interleukin (IL)-1, IL-2, IL-6, and tumor necrosis factor-alpha) (Sadek et al 2017) as well as in rabbits infected with Mycobacterium tuberculosis (including vascular endothelial growth factor, platelet derived growth factor, IL-17A, and IL-18) (Dehnad et al 2016). Significant down-regulation of serum IL-7 was identified in acute human cholangitis (Suwa et al 2017), and substantial increase in plasma IL-6 level was observed in mice infected with influenza A virus (Chockalingam et al 2016) as well as in human patients infected with Trypanosoma brucei rhodesiense (Kato et al 2015). In fact, IL-6 has also been identified as a biomarker for ischemic stroke (Doll et al 2014), differential diagnosis of pancreatic cancer (Shaw et al 2014), and congenital heart D r a f t disease (Nassef et al 2014).…”
mentioning
confidence: 99%